2005
DOI: 10.1503/cmaj.1031527
|View full text |Cite
|
Sign up to set email alerts
|

An approach to the management of unintentional weight loss in elderly people

Abstract: UNINTENTIONAL WEIGHT LOSS, or the involuntary decline in total body weight over time, is common among elderly people who live at home. Weight loss in elderly people can have a deleterious effect on the ability to function and on quality of life and is associated with an increase in mortality over a 12-month period. A variety of physical, psychological and social conditions, along with age-related changes, can lead to weight loss, but there may be no identifiable cause in up to one-quarter of patients. We revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
143
0
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(166 citation statements)
references
References 98 publications
6
143
0
6
Order By: Relevance
“…In conclusion, our findings highlight the importance of monitoring changes in weight in older persons with poor cognition with the aim of reducing the negative consequences of loss of fat and muscle, such as increased mortality, morbidity and progressive disability [36]. It will, therefore, be important to develop strategies to prevent weight and muscle loss.…”
Section: Discussionmentioning
confidence: 71%
“…In conclusion, our findings highlight the importance of monitoring changes in weight in older persons with poor cognition with the aim of reducing the negative consequences of loss of fat and muscle, such as increased mortality, morbidity and progressive disability [36]. It will, therefore, be important to develop strategies to prevent weight and muscle loss.…”
Section: Discussionmentioning
confidence: 71%
“…111 A neutral effect on body weight represents an advantage in other clinical settings, for example in elderly patients who are at risk of unintentional weight loss. 112,113 Certainly, as metformin did not reduce body weight in the UKPDS, it is unlikely that its effects on glycemia or cardiovascular outcomes resulted from a weight-dependent mechanism, in contrast to antiobesity drugs which rely on weight loss for a substantial proportion of their effects on cardiometabolic risk factors. 22,23,25 While the favorable effects of metformin on body weight are modest, considerations relating to body weight have profoundly affected its therapeutic use.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium and vitamin D intake should be optimized. Given the changes in appetite and satiety, it has also been suggested that snacking during the day may be beneficial [1,83].…”
Section: Management Of Undernutritionmentioning
confidence: 99%
“…The evidence supporting any pharmacologic agent for the treatment of weight loss is limited [1]. Medications trialed to date, such as megesterol acetate, dronabinol, and human recombinant growth hormone have serious side effects especially in frail older people in whom weight loss is commonly seen and therefore cannot be recommended for routine clinical use at this stage.…”
Section: Management Of Undernutritionmentioning
confidence: 99%